Soundscape of the West Lake Scenic Area with profound cultural background a case study of Evening Bell Ringing in Jingci Temple, China - Ge, Jian; Guo, Min; Yue, Miao (Journal of Zhejiang University. A. Science, 2013)
From the case study of Evening Bell Ringing at Nanping Hill, one ofthe West Lake Cultural Landscapes in Hangzhou, China, we investigated the soundscape of a scenic area with a profound cultural background. First, we conducted the soundscape physical index of the area in both winter and spring seasons to analyze its objective graphical expression. Second, we focused on people＇s reactions to the soundscape in order to obtain a subjective evaluation of each component in the soundscape and integrated environment. Then, the relationship between the objective data and the subjective evaluation was analyzed. Finally, the impacts of the natural environment, history, and cultural factors on the evaluation of the Jingci Temple soundscape were studied. It was found that natural sounds, cultural sounds, and historic sounds were widely acclaimed in people＇s subjective feelings, which indicated the close relationships among historical and cultural background, soundscape, and natural environment. Thus, the conclusion was made that soundscape should be consistent with the local natural environment and the historical and cultural background.